P.208 Pilot Study of a Multi-center, Randomized, Blinded, Placebo-Controlled Trial of Shunt Surgery in Idiopathic Normal Pressure Hydrocephalus. (November 2021) - Hamilton, MG; Williams, M; Holubkov, R; Nagel, S; Wisoff, J; McKhann, G; Zwimpfer, T; Edwards, R; Malm, J; Moghekar, A; Eklund, A; Golomb, J; et al.
Abstract : Background: To describe preliminary results of a multi-center, randomized, blinded, placebo-controlled, pilot trial of shunt surgery in idiopathic normal pressure hydrocephalus (iNPH). Methods: Five sites of the Adult Hydrocephalus Clinical Research Network (AHCRN) randomized 18 patients scheduled for ventriculoperitoneal shunting based on CSF-drainage response. Patients were randomized to a Codman® Certas® Plus valve with SiphonGuard at either setting 4 (Active, N=9) or setting 8/"virtual off" (Placebo, N=9). Patients and assessors were blinded to the shunt setting. Outcomes included 10-meter gait velocity, cognitive function, and bladder activity scores. The prespecified primary analysis compared changes in 4-month gait velocity in the Active versus Placebo groups. Placebo-set shunts were then blindly adjusted to the active setting and all patients underwent 8 and 12-month post-surgical assessment. Results: At 4-months, gait velocity increased by 0.28±0.28m/s in the Active Group and 0.04±0.17m/s in the Placebo Group (p=0.071). Overactive Bladder (OAB-q) scores significantly improved in the Active versus Placebo groups (p=0.007). At 8 months, Placebo gait velocity increased by 0.36±0.27m/s and was comparable to the Active Group (0.40±0.20m/s; p=0.56). Conclusions: This AHCRN study shows a trend suggesting gait velocity improves more at an Active shunt setting than a Placebo shunt setting and demonstrates the feasibility of a placebo-controlled trial in iNPH.